Business cycle persistence in developing countries: How successful is a DSGE model with a vertical production chain and sticky prices? - Rachel Male (Queen Mary University of London, School of Economics and Finance, 2010)
It is well documented that business cycles of developed countries are characterised by persistent output fluctuations, and this has been the subject of much theoretical interest. However, the case for developing countries has been somewhat neglected in the literature. This paper addresses this imbalance, revealing that whilst both developed and developing countries exhibit persistent output fluctuations, there is a significant positive relationship between output persistence and level of economic development. This relationship was successfully modelled using a vertical production chain DSGE model (Huang and Liu, 2001). This model lends itself to such an analysis, as by altering the number of production stages (N) it is possible to represent economies at different levels of development. However, calibration of low input-output (Ú) parameter values for the US and UK effectively inhibited the model from generating enough persistence to match that observed in these countries. Nonetheless, after abstracting from the US and UK results, there was found to be a strong significant positive relationship between the magnitude of output persistence generated by the model and economic development. A final very significant finding of this analysis is that the model overestimates output persistence in high inflation countries and underestimates output persistence in low inflation countries. This has important implications not only for this model, but also for any economist attempting to construct a business cycle model capable of replicating the observed patterns of output persistence.
Keywords: E31; E32; E52; 330; output persistence; vertical production chain; staggered price contracts; economic development; inflation; Konjunktur; Gesamtwirtschaftliche Produktion; Volatilität; Vertikale Konzentration; Entwicklungsstufe; Dynamisches Gleichgewicht; Welt